2019
DOI: 10.1002/jip.1529
|View full text |Cite
|
Sign up to set email alerts
|

Language and eyewitness suggestibility

Abstract: During forensic interviews, eyewitnesses are to retrieve correct information from memory. Cognitive load should be high, leading to risks of giving in to suggestive questions and difficulties in memory retrieval generally. Testifying in a non‐native vs. native language may require even more cognitive effort due to the need to inhibit the interference of the native language. Such witnesses may also be more motivated to appear credible because they often belong to ethnic outgroups relative to forensic profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
0
14
2
Order By: Relevance
“…(2012) found that a greater cognitive load (not language‐related) increased suggestibility in a non‐forensic context. In another study, participants freely recalled a mock crime either in their native language (Swedish) or in their second language (English; Alm et al., 2019). Afterward, they completed a suggestibility measure that included leading questions and were asked how effortful the task was.…”
Section: Forensic Interviews With L2 Speakersmentioning
confidence: 99%
See 3 more Smart Citations
“…(2012) found that a greater cognitive load (not language‐related) increased suggestibility in a non‐forensic context. In another study, participants freely recalled a mock crime either in their native language (Swedish) or in their second language (English; Alm et al., 2019). Afterward, they completed a suggestibility measure that included leading questions and were asked how effortful the task was.…”
Section: Forensic Interviews With L2 Speakersmentioning
confidence: 99%
“…Afterward, they completed a suggestibility measure that included leading questions and were asked how effortful the task was. Participants who recalled in their second language were more suggestible and perceived their cognitive effort to be higher than those who recalled the crime in their first language (Alm et al., 2019), suggesting that recalling a crime in their second language may have had a negative impact on memory, in part because of their increased cognitive load.…”
Section: Forensic Interviews With L2 Speakersmentioning
confidence: 99%
See 2 more Smart Citations
“…The most pertinent of which is reduced language ability, which makes reporting more difficult (Abutalebi, 2008). Consequently, compared with those providing statements in their first language, research shows that people recalling events in their second language provide shorter statements (Ewens et al, 2017; Ewens, Vrij, Leal, Mann, Jo, & Fisher, 2016; Ewens, Vrij, Leal, Mann, Jo, Shaboltas, et al, 2016), though not necessarily less accurate ones (Alm et al, 2019). Other research suggests that people providing statements in their second language are more nervous (Akehurst et al, 2018), suggestible (Alm et al, 2019) and appear as less credible (Frumkin, 2007; Lindholm, 2008) than those providing statements in their first language.…”
Section: Introductionmentioning
confidence: 99%